2021
DOI: 10.1016/j.jamcollsurg.2021.08.184
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Preoperative Embolization of the Splenic Artery in Patients Undergoing Splenectomy for Immune Thrombocytopenic Purpura

Abstract: p<0.0001) whereas a cancer diagnosis more likely used both telemedicine and in-person (55%). Median time from referral to encounter significantly decreased after SIP for both telemedicine only (7 to 3 days) and telemedicine combined with in-person (5 to 2 days), compared to in-person only (7 to 6 days, p<0.0001). Post-SIP, postoperative encounters for all categories of surgical acuity were mainly telemedicine (72%) compared to pre-SIP (45%).CONCLUSION: Telemedicine encounters can provide efficient preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Newer surgical energy devices, including the Valley Lab LigaSure vessel‐sealing system and Ethicon Harmonic Scalpel, reduce blood loss and operative time 15,16 . Three investigators have reported a reduced number of bleeding complications when preoperative splenic artery embolization was performed 17–19 . Elective splenectomy allows vaccination to be completed at least 2 weeks preoperatively; if vaccination has not been performed preoperatively, an 8‐week interval is recommended prior to postoperative vaccination of the patient 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer surgical energy devices, including the Valley Lab LigaSure vessel‐sealing system and Ethicon Harmonic Scalpel, reduce blood loss and operative time 15,16 . Three investigators have reported a reduced number of bleeding complications when preoperative splenic artery embolization was performed 17–19 . Elective splenectomy allows vaccination to be completed at least 2 weeks preoperatively; if vaccination has not been performed preoperatively, an 8‐week interval is recommended prior to postoperative vaccination of the patient 20 …”
Section: Discussionmentioning
confidence: 99%
“…15,16 Three investigators have reported a reduced number of bleeding complications when preoperative splenic artery embolization was performed. [17][18][19] Elective splenectomy allows vaccination to be completed at least 2 weeks preoperatively; if vaccination has not been performed preoperatively, an 8-week interval is recommended prior to postoperative vaccination of the patient. 20 Prior research suggests that patients can have a sustained response to either medical therapy or splenectomy, though studies suggest a higher percentage of surgical patients have a sustained response compared to patients who receive medical therapy for ITP.…”
Section: Discussionmentioning
confidence: 99%